Heptamethine Cyanine–Based Application for Cancer Theranostics - Zhang, Lei; Jia, Hang; Liu, Xuqian; Zou, Yaxin; Sun, Jiayi; Liu, Mengyu; Jia, Shuangshuang; Liu, Nan; Li, Yanzhang; Wang, Qun (Frontiers in Pharmacology, 2022)
Cancer is the most common life-threatening malignant disease. The future of personalized cancer treatments relies on the development of functional agents that have tumor-targeted anti-cancer activities and can be detected in tumors through imaging. Cyanines, especially heptamethine cyanine (Cy7), have prospective application because of their excellent tumor targeting, high quantum yield, low tissue auto-fluorescence, long absorption wavelength, and low background interference. In this review, the application of Cy7 and its derivatives in tumors is comprehensively explored. Cy7 is enormously acknowledged in the field of non-invasive therapy that can “detect” and “kill” tumor cells via Near-infrared fluorescence (NIRF) imaging, photothermal therapy (PTT) and photodynamic therapy (PDT). Furthermore, Cy7 is more available and has excellent properties in cancer theranostics by the presence of multifunctional nanoparticles via fulfilling multimodal imaging and combination therapy simultaneously. This review provides a comprehensive scope of Cy7’s application for cancer NIRF imaging, phototherapy, nanoprobes-based combination therapy in recent years. A deeper understanding of the application of imaging and treatment underlying Cy7 in cancer may provide new strategies for drug development based on cyanine. Thus, the review will lead the way to new types with optical properties and practical transformation to clinical practice.